Identifikasi Penerapan Pembelajaran Teaching At The Right Level Berdasarkan Tingkat Kemampuan Kognitif Siswa Kelas V di SD Inpres Bumi Sagu - Lintuman, Lusiani; Herlina, Herlina; Muchdar, Muchdar (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
This research aims to determine the level of ability of students in class V of SD Inpres Bumi Sagu, to find out the implementation of Teaching at The Right Level (TaRL) learning in class V of SD Inpres Bumi Sagu and to find out what challenges are experienced in implementing learning according to the Teaching at The Right Level (TaRL) approach in class V of SD Inpres Bumi Sagu. This research is qualitative research. The subjects in this research were 15 class V students. Based on the results of research that has been carried out by observing during the learning process for class V students and studying documents from teachers. The results obtained, namely the results of the diagnostic assessment, showed that of the 15 students, the majority of students were at a high level of cognitive ability, namely 46.6%, with some students at a medium level, 40% and students at a low level, namely 13,3%. Based on the results of observations, it is known that teachers implement the TaRL approach through three main steps: the first step is identifying abilities, the second step is grouping, and the third step is differentiated learning. Based on the results of interviews with teachers, the challenges faced by teachers in implementing TaRL are the need to be more active in preparing initial assessments, managing classrooms that support differentiated learning, overcoming the discipline of students who tend to play during learning, and teachers' difficulties in creating LKPD that are appropriate to students' ability levels.